Comparative investigation of different types of nickel foam samples for application in supercapacitors and other electrochemical devices - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2021)
Nickel foam is widely used as a current lead/current collector and the basis of nickel hydroxide electrodes for various electrochemical devices – batteries, hybrid supercapacitors, devices for electrocatalytic oxidation of organic substances. The characteristics of commercial samples of nickel foam produced by Novomet-Perm (Russian Federation) obtained by electroless and then electrochemical nickel plating and Linyi Gelon LIB Co Ltd (China) obtained by electroless nickel plating were studied. The nature of passivity was determined by forming model samples of electrochemical and electroless nickel on a steel base. For the passive sample, activation was carried out by applying a layer of electrochemical nickel from an impact nickel plating solution. Activated, non-activated samples of nickel foam, as well as model samples, were studied by the methods of cyclic voltammetry and galvanostatic charge-discharge cycling in the supercapacitor mode. Comparative analysis of Chinese-made and Russian-made nickel foam samples showed significant passivity of the former – in cyclic voltammetry, the activity was 4.8 times lower, with galvanostatic charge-discharge cycling – 2.59 times lower. It was suggested that high passivity was determined by the fact that the sample consisted of Ni-P or Ni-B alloy. This assumption was proved by the method of natural simulation. The electrochemical activity of electroless nickel was 1.25 times lower than that of electrochemical nickel (according to cyclic voltammetry data) and 1.58 times lower (according to galvanostatic cycling data). For the first time, Chinese-made nickel foam (electroless nickel) was activated by applying a layer of electrochemical nickel from an impact nickel electrolyte. The high activation efficiency was shown as follows – on the cyclic curve, the specific current of the anodic peak increased 8.71 times, and with galvanostatic cycling, the increase in specific capacity was from 1.73 times (at i=120 mA/cm2) to 4.84 times (at i=20 mA/cm2)